Can Democrats and Republicans like each other? Depends on how you define “American” - Toprakkiran, Selin; Gordils, Jonathan; Jamieson, Jeremy P. (Frontiers in Social Psychology, 2024)
Democrats and Republicans increasingly demonstrate negative intergroup attitudes, posing a threat to bipartisan progress. Based on the Common Ingroup Identity Model, people from different political groups can simultaneously identify with a superordinate group, such as a national identity. This has the potential to ameliorate negative intergroup attitudes, though high levels of national identity are also associated with authoritarianism and intolerance. How can a common national identity improve relations between Democrats and Republicans? In this observational study (N = 1,272), Democrats and Republicans differed in how they defined what it means to be American, and higher American identity was related to more positive attitudes toward members of the other party. Most importantly, this relationship was moderated by participants' definition of what it means to be “American,” regardless of party or political orientation. Those who defined what it means to be American in more restrictive terms (i.e., U.S.-born, English-speaking, and Christian) reported less positive attitudes toward members of the other political party as their identification as an American became stronger. Taken together, our results suggest that strengthening national identity might be key to improving attitudes between Democrats and Republicans, as long as this identity is inclusive.